Deviation Analyses of Computer-Assisted, Template-Guided Mandibular Reconstruction With Combined Osteotomy and Reconstruction Pre-Shaped Plate Position Technology: A Comparative Study - Chen, Jie; Zhang, Ruipu; Liang, Ye; Ma, Yujie; Song, Saiwen; Jiang, Canhua (Frontiers in Oncology, 2021)
Background: Computer-assisted and template-guided mandibular reconstruction provides higher accuracy and less variation than conventional freehand surgeries. The combined osteotomy and reconstruction pre-shaped plate position (CORPPP) technique is a reliable choice for mandibular reconstruction. This study aimed to evaluate the accuracy of CORPPP-guided fibular flap mandibular reconstruction and analyze the possible causes of the deviations. Patients and Methods: From June 2015 to December 2016, 28 patients underwent fibular flap mandibular reconstruction. Virtual planning and personalized CORPPP-guided templates were applied in 15 patients while 13 patients received conventional freehand surgeries. Deviations during mandibulectomy and fibular osteotomy, overall and triaxial deviation of the corresponding mandibular anatomical landmarks were measured by superimposing the pre- and postoperative virtual models. Results: The deviation of the resection line and resection angle was 1.23 ± 0.98 mm and 4.11 ± 2.60°. The actual length of fibula segments was longer than the designed length in 7 cases (mean: 0.35 ± 0.32 mm) and shorter in 22 cases (mean: 1.53 ± 1.19 mm). In patients without ramus reconstruction, deviations of the ipsilateral condylar head point (Co.), gonion point (Go.) and coracoid process point (Cor.) was 6.71 ± 3.42 mm, 5.38 ± 1.71 mm, 11.05 ± 3.24 mm in freehand group and 1.73 ± 1.13 mm, 1.86 ± 0.96 mm, 2.54 ± 0.50 mm in CORPPP group, respectively, with significant statistical differences (p < 0.05). In patients with ramus reconstruction, deviations of ipsilateral Co. and Go. was 9.79 ± 4.74 mm vs 3.57 ± 1.62 mm (p < 0.05), and 15.17 ± 6.53 mm vs 4.36 ± 1.68 mm (p < 0.05) in freehand group and CORPPP group, respectively. Conclusion: Mandibular reconstructions employing virtual planning and personalized CORPPP-guided templates show significantly higher predictability, convenience, and accuracy of mandibular reconstruction compared with conventional freehand surgeries. However, more clinical cases were required to for further dimensional deviation analysis. The application and exploration of clinical practice would also continuously improve the design of templates.